2016
DOI: 10.1186/s12917-016-0649-0
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Austrian veterinarians towards euthanasia in small animal practice: impacts of age and gender on views on euthanasia

Abstract: BackgroundEuthanasia of pets has been described by veterinarians as “the best and the worst” of the profession. The most commonly mentioned ethical dilemmas veterinarians face in small animal practice are: limited treatment options due to financial constraints, euthanizing of healthy animals and owners wishing to continue treatment of terminally ill animals. The aim of the study was to gain insight into the attitudes of Austrian veterinarians towards euthanasia of small animals. This included assessing their a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 27 publications
4
63
0
6
Order By: Relevance
“…Several studies have found that euthanasia of healthy and sick animals, dealing with clients with financial limitations and being asked to continue treatment when you believe euthanasia is needed are all stressful situations (Batchelor and McKeegan 2012, Crane and others 2015, Hartnack and others 2016). What makes a stressful situation give rise to moral distress is not clear, but social support and institutional structures are likely to play a part.…”
Section: What Is Moral Distress?mentioning
confidence: 99%
“…Several studies have found that euthanasia of healthy and sick animals, dealing with clients with financial limitations and being asked to continue treatment when you believe euthanasia is needed are all stressful situations (Batchelor and McKeegan 2012, Crane and others 2015, Hartnack and others 2016). What makes a stressful situation give rise to moral distress is not clear, but social support and institutional structures are likely to play a part.…”
Section: What Is Moral Distress?mentioning
confidence: 99%
“…Few veterinarians could name specific tools they use to define and address these problems, and their prior education may not have included any instruction on these tools (7, 9, 11). The first additions to this tool kit, if not already acquired, should be an ethical decision-making framework , a good communication system , and quality of life assessment and consent tools .…”
Section: Euthanasia Decisions Are Stressful For Veterinariansmentioning
confidence: 99%
“…The presence of experienced colleagues at worknot only to discuss the medical point of view but also to provide mutual support for several difficult euthanasia cases highlights the role of a 'team' to provide support in stressful situations [60].…”
Section: 22mentioning
confidence: 99%
“…In a more recent study in 2016 of practising veterinary surgeons' attitudes to euthanasia [60], coping strategy statements (which had been carefully chosen following extensive literature reviews), were presented to the vets and there was strong agreement and linkage between the following statements: 'It is easier for me to deal with euthanasia if I know that the animal would only have lived on for a short time'.…”
Section: 22mentioning
confidence: 99%
See 1 more Smart Citation